Viability and Biomechanics of Diced Cartilage Blended With Platelet-Rich Plasma and Wrapped With Poly (Lactic-Co-Glycolic) Acid Membrane. Issue 6 (September 2017) - Liao, Jun-Lin; Chen, Jia; He, Bin; Chen, Yong; Xu, Jia-Qun; Xie, Hong-Ju; Hu, Feng; Wang, Ai-Jun; Luo, ChengQun; Li, Qing-Feng; Zhou, Jian-Da
Abstract : Objectives: The objective of this study was to investigate the viability and biomechanics of diced cartilage blended with platelet-rich plasma (PRP) and wrapped with poly (lactic-co-glycolic) acid (PLGA) membrane in a rabbit model. Methods: A total of 10 New Zealand rabbits were used for the study. Cartilage grafts were harvested from 1 side ear. The grafts were divided into 3 groups for comparison: bare diced cartilage, diced cartilage wrapped with PLGA membrane, and diced cartilage blended with PRP and wrapped with PLGA membrane. Platelet-rich plasma was prepared using 8 mL of auricular blood. Three subcutaneous pockets were made in the backs of the rabbits, and the grafts were placed in these pockets. The subcutaneous implant tests were conducted for safety assessment of the PLGA membrane in vivo. All of the rabbits were sacrificed at the end of 3 months, and the specimens were collected. The sections were stained with hematoxylin and eosin, toluidin blue, and collagen II immunohistochemical. Simultaneously, biomechanical properties of grafts were assessed. Results: This sample of PLGA membrane was conformed to the current standard of biological evaluation of medical devices. Moderate resorption was seen at the end of 3 months in the gross assessment in diced cartilage wrapped with PLGA membrane, while diced cartilage blended with PRP had no apparent resorption macroscopically and favorable viability in vivo after 3 months, and the histological parameters supported this. Stress–strain curves for the compression test indicated that the modulus of elasticity of bare diced cartilage was 7.65 ± 0.59 MPa; diced cartilage wrapped with PLGA membrane was 5.98 ± 0.45 MPa; and diced cartilage blended with PRP and wrapped with PLGA membrane was 7.48 ± 0.55 MPa, respectively. Conclusions: Diced cartilage wrapped with PLGA membrane had moderate resorption macroscopically after 3 months. However, blending with PRP has beneficial effects in improving the viability of diced cartilages. Additionally, the compression modulus of diced cartilage blended with PRP and wrapped with PLGA membrane was similar to bare diced cartilage.